Feline Endometrial Adenocarcinoma in Females <1 Year Old: A Description of Four Cases. Issue 5 (9th July 2013) - Payan‐Carreira, R; Saraiva, AL; Santos, T; Vilhena, H; Sousa, A; Santos, C; Pires, MA
Contents Uterine neoplasms of epithelial origin are rare in cats and most often are described in older females. Yet, in less than 2 years, four ovariohysterectomy specimens were submitted from different practices to the Laboratory of Histology and Anatomical Pathology, at UTAD (Vila Real, Portugal), that emitted a diagnosis of feline endometrial adenocarcinoma. Untypically, all the females were aged <1 year old at the surgery. Access to the clinical files was requested to document the clinical features of the four cases, including any complementary data available, to construct the present case reports. The clinical situation developed with discrete signs, but vulvar discharge was present in three cases, ranging from bloody to brownish or colourless, and from purulent to mucous. The females were in dioestrus, although the oestrus remained unperceived in most cases. In this study, the four clinical situations are described and discussed on the basis of available literature, highlighting the aspects that may impair an early diagnosis and that may favour the progression of the disease and also that age should not be an excluding criteria when analysing the differential diagnosis list.